CASH MANAGEMENT AND FINANCIAL PERFORMANCE OF LISTED FIRMS IN NIGERIA (Journal of Global Accounting, 2025)
The study examined the effect of cash management on financial performance of listed insurance firms in Nigeria. The management of insurance business in Nigeria is a serious challenge despite the relevance of this service in the country due to a lot of problems that are entailed in insurance business. The study specifically seeks to determine the effect of cash management on net assets per share and to ascertain the impact of cash management on market price per share of listed insurance firms in Nigeria. Cash management was represented by the ratio of cash and cash equivalent to total assets while financial performance on the other hand was proxy in the study with net assets per share and market price per share. Statistical test of parameter estimates was conducted using Panel least squares regression method. Ex Post Facto design was adopted and data for the study were obtained from the Nigerian Exchange Group Factbook and published annual financial reports of listed insurance firms in Nigeria from 2015-2023. The study revealed that cash management has positive and significant effect on firm performance. Furthermore, the study came to conclusion that cash management improves financial performance in listed insurance firms Nigeria. It is therefore recommended, among others that managers should consider the financial condition of a firm when determining the optimum cash liquidity due to its different effects since optimal cash management enhances firm net assets value and market share.
Keywords: Cash Management; Financial Performance; Listed Insurance Firms; Market Price Per Share; Net Assets Per Share